2021
DOI: 10.1210/clinem/dgab238
|View full text |Cite
|
Sign up to set email alerts
|

Serum Inflammation-based Scores in Endocrine Tumors

Abstract: Context Serum inflammation-based scores reflect systemic inflammatory response and/or patients’ nutritional status, and may predict clinical outcomes in cancer. While these are well-described and increasingly used in different cancers, their clinical usefulness in the management of patients with endocrine tumors is less known. Evidence acquisition A comprehensive PubMed search was performed using the terms “endocrine tumor”, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 135 publications
0
12
0
Order By: Relevance
“…THCA accounts for more than 95% of endocrine cancer, and most are well-differentiated arising from follicular epithelial cells [15]. Although THCA patients have better clinical outcomes, a number of patients still develop local recurrence with or without cervical lymph node metastasis or distant metastases [16].…”
Section: Discussionmentioning
confidence: 99%
“…THCA accounts for more than 95% of endocrine cancer, and most are well-differentiated arising from follicular epithelial cells [15]. Although THCA patients have better clinical outcomes, a number of patients still develop local recurrence with or without cervical lymph node metastasis or distant metastases [16].…”
Section: Discussionmentioning
confidence: 99%
“…1). [4][5][6] In recent years, extensive research has revealed the intricate connection between tumors and inflammation. [7][8][9][10] It has been found that the molecular and cellular mechanisms linking inflammation and cancer involve 2 pathways.…”
Section: The Relationship Between Tumors and Inflammationmentioning
confidence: 99%
“…Elevations in circulating platelet-to-lymphocyte ratios are often associated with inflammation and poor outcomes along with being linked to infections, inflammatory diseases, liver disease and cancer (140)(141)(142)(143)(144)(145)(146). The predictive value indicative of poor outcomes linked to elevated platelet-to-lymphocyte ratios has shown clear associations with liver transplantation, particularly when performed for hepatocellular carcinoma and liver metastasis (147)(148)(149)(150)(151)(152).…”
Section: Platelet-to-lymphocyte Ratiosmentioning
confidence: 99%